2014
DOI: 10.1016/j.optom.2014.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Symptomatology associated with accommodative and binocular vision anomalies

Abstract: There is a wide disparity of symptoms related to accommodative and binocular dysfunctions in the scientific literature, most of which are associated with near vision and binocular dysfunctions. The only psychometrically validated questionnaires that we found (n=3) were related to convergence insufficiency and to visual dysfunctions in general and there no specific questionnaires for other anomalies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
86
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(98 citation statements)
references
References 54 publications
8
86
1
3
Order By: Relevance
“…For each dysfunction, the type and number of complaints reported by patients have been detailed. The categories of symptom are those described by García‐Muñoz, Carbonell‐Bonete and Cacho‐Martinez in a current scoping review, in which the different types of symptoms may be related to accommodative and binocular anomalies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For each dysfunction, the type and number of complaints reported by patients have been detailed. The categories of symptom are those described by García‐Muñoz, Carbonell‐Bonete and Cacho‐Martinez in a current scoping review, in which the different types of symptoms may be related to accommodative and binocular anomalies.…”
Section: Resultsmentioning
confidence: 99%
“…Data were also collected on the symptoms reported by the subjects so that they were asked if they had any symptoms. For that, we used the categories of symptoms described by García‐Muñoz, Carbonell‐Bonete and Cacho‐Martínez in a recent scoping review (considering articles over the last 30 years), in which they indicated the different types of symptoms which have been associated with accommodative and binocular dysfunctions. We showed the list of categories of symptoms on a page and patients were asked if they were suffering any of these symptoms related to their vision.…”
Section: Methodsmentioning
confidence: 99%
“…These dysfunctions challenge near‐activity demands. Symptoms may include blurred vision, reading problems, headache, diplopia, and in many cases, difficulty in maintaining comfortable vision for a long time . Also, these visual disorders are associated with musculoskeletal discomfort in the neck and shoulder .…”
Section: Introductionmentioning
confidence: 99%
“…This abnormal situation produces prolonged activation of the extrinsic and intrinsic muscles of the eye with distortion and imbalance in visual behavior, resulting in accommodative nonstrabismic binocular dysfunctions . The lack of efficiency of the visual system causes diverse symptomatology, including eye strain and performance problems . Similarly, it increases musculoskeletal discomfort in the neck area, so that visual symptoms and muscle complaints coexist at the same time .…”
Section: Introductionmentioning
confidence: 99%